An Analysis of Students’ Difficulties in Listening Comprehension: A Descriptive Study at English Language and Literature Department FBS UNP - Lini Diora; Rusdi Noor Rosa (Universitas Negeri Padang, 2020)
This research was aimed to find out the difficulties that mostly faced by students in listening comprehension and the factors which cause the difficulties at English language and literature department FBS UNP. This study employed descriptive qualitative research method. The subjects of this research were K-2 Class which consists of 32 students selected by using cluster sampling technique. The data was collected from questionnaire and interview. The researcher distributed the questionnaire to all members of the class. After that, the researcher chose six students to be interviewed. The results of this study showed that the difficulties that the students faced in listening comprehension were related into three categories, they were the listening material, the listener, and the physical setting. Besides, the factors which cause students’ difficulties in listening comprehension were depend on others, shame to ask the lecturer about the material, having emotional disturbances, the lecturer explains the material too quickly, lack of reward and reinforcement, and unfocused.